A method to remove cellulose from rich organic samples to analyse microplastics. (1st February 2022) - Egea-Corbacho, Agata; Martín-García, Ana Pilar; Franco, Ana Amelia; Albendín, Gemma; Arellano, Juana María; Rodríguez, Rocío; Quiroga, José María; Coello, María Dolores
Abstract: Knowing the amount of microplastics that currently reach wastewater is extremely important today. Furthermore, carrying out a good quantification and detection of the type of plastic provides valuable information. However, the wastewater is loaded, in addition to a high concentration of organic matter, with a high concentration of cellulose at the treatment plant influent, which seriously hinders detection, quantification and classification of microplastics. The abundance of cellulose materials makes them possible to become false positives for microplastics. Numerous studies on the analysis of microplastics in different matrices show how to remove organic matter from samples, but there are very few studies on the removal of cellulose, which is also found in the samples and hinders their analysis. This study offers a method that combines, for the analysis of microplastics, the already known advanced oxidation treatments for the elimination of organic matter with the novel cellulose removal treatment of the samples with the aim of reducing the amount of cellulose in the influent samples of conventional wastewater treatment plants. To remove the cellulose, 40 mL of a solution of urea 8%, sodium hydroxide 8% and thiourea 6.5% (by weight) were added for every 100 mg of dry sample. The beakers were placed in the freezer at minus 20 °C for 40 min and were then placed in agitation until they reached room temperature. After that, the samples were passed through a 53 μm mesh sieve. They were washed 15 times with 30 mL of ultra-pure water. The method is called UTS because of the acronym of its reagents (Urea/Thiourea/Sodium Hydroxide). By using the UTS method it is possible to reduce almost completely the cellulose residues from the influent sewage, and sludge samples by 97.6% in a second UTS treatment and 98.2% in a third UTS treatment. In all cases analyzed, the microplastics were identified as high density polyethylene (HDPE) with correlation indices higher than 0.97, which shows that the treatment is harmless for this type of plastic material. The UTS method in combination with the WPO is an efficient and effective method for the analysis of microplastics in different matrices where cellulose and organic matter may cause possible interferences. Graphical abstract: Image 1 Highlights: Cellulose in wastewater and sludge causes interference in microplastic analysis. A new method for removal cellulose in the analysis of microplastics is reported. The study covers the behaviour of samples of synthetic, wastewater and sludge samples. Reducing the cellulose by 97.6% in a second treatment with the method proposed.